﻿Logistical challenges with an emphasis on organizing specialized triage in the conditions of a newly emerging, epidemiologically significant infectious pathogen for humans - SARS-CoV2 - Diana Pantileeva; Diana Rangelova; Petar Atanasov; Snezhinka Mircheva; Ivaylo Ivanov; Maria Chaneva; Danka Obreshkova; Stefka Ivanova; Stoyan Milanov; Krasimira Kazalakova; Valentin Dimitrov; Valentina Petkova; et al. (Pensoft Publishers, 2023)
Background: UMHATEM "N.I. Pirogov" Sofia, is one of the largest and busiest hospitals for emergency medical care in Bulgaria. It is the legal successor of the former Institute of Emergency Medicine "N.I. Pirogov", and it can be said that at the moment it is the only diagnostic- therapeutic, prophylactic and scientific-educational structure of this type within the Bulgarian healthcare system. The concept of adequate functioning and development of this type of hospital does not consider structuring an Infectious Diseases diagnostic-treatment unit. This reality makes necessary the formation of a radically different organization for the admission and treatment of patients in the hospital, both for those with symptoms of Covid 19 and for all other emergency patients. The organization created in this way must absolutely guarantee safety for both streams of patients. In the conditions of a pandemic, in case of a real threat to public health, the main task of triage in the Emergency Department is to establish indications for urgent hospitalization, or to refuse it in the absence of indications. The characteristic course of the disease, the prolonged treatment, the manifestations within the so-called "post-Covid syndrome", require serious planning not only of the diagnostic-treatment and rehabilitation period, but also adequate monitoring in the first months after the patient's discharge. Within the national reorganization measures, during the determined periods, the main changes concerning the MED (Multi-profile emergency department) of Pirogov are implemented, with an emphasis on the formation of a specialized triage for the diagnosis and clinical evaluation of patients with a coronavirus infection. The main goal is the adequate diagnosis, treatment and follow-up of patients with coronavirus infection who have passed through the organized Covid-triage in a period of extreme pressure on the emergency structures and on the hospital system in the country as a whole. Objective: For a MED, which at the time of declaring an epidemic situation does not have a concept for the diagnosis and treatment of infectious diseases, to systematize the main urgently implemented organizational and structural changes, which turned out to be absolutely necessary to meet a newly emerging epidemiologically significant infectious disease. Aims: To systematize the organizational changes imposed by the situation and urgently implemented in the MED (multi-profile emergency department). To systematize the structural changes imposed by the situation and urgently implemented in the work of the MED. To analyze the organizational and structural changes carried out in this way and to differentiate the main difficulties caused by the regulations existing at the time of the announcement of the epidemic situation.